In vivo Profiling of the Alk Proximitome in the Developing Drosophila Brain. Issue 23 (19th November 2021) - Uçkun, Ezgi; Wolfstetter, Georg; Anthonydhason, Vimala; Sukumar, Sanjay Kumar; Umapathy, Ganesh; Molander, Linnea; Fuchs, Johannes; Palmer, Ruth H.
Graphical abstract: Highlights: BioID identifies components of the Alk proximitome in Drosophila larval brain. Next-generation variants, TurboID and miniTurbo, display superior proximity labeling. TurboID and miniTurbo efficiently label the Alk proximitome at endogenous Alk levels. TurboID and miniTurbo allow proximity labeling during Drosophila embryogenesis. BioID identifies the Drosophila SHP2 homologue as a modulator of Alk signaling. Abstract: Anaplastic lymphoma kinase (Alk) is an evolutionary conserved receptor tyrosine kinase belonging to the insulin receptor superfamily. In addition to its well-studied role in cancer, numerous studies have revealed that Alk signaling is associated with a variety of complex traits such as: regulation of growth and metabolism, hibernation, regulation of neurotransmitters, synaptic coupling, axon targeting, decision making, memory formation and learning, alcohol use disorder, as well as steroid hormone metabolism. In this study, we used BioID-based in vivo proximity labeling to identify molecules that interact with Alk in the Drosophila central nervous system (CNS). To do this, we used CRISPR/Cas9 induced homology-directed repair (HDR) to modify the endogenous Alk locus to produce first and next generation Alk::BioID chimeras. This approach allowed identification of Alk proximitomes under physiological conditions and without overexpression. Our results show that the next generation of BioID proteins (TurboID and miniTurbo) outperform the first generation BirA* fusion in terms of labeling speed and efficiency. LC-MS3-based BioID screening of Alk TurboID and Alk miniTurbo larval brains revealed an extensive neuronal Alk proximitome identifying numerous potential components of Alk signaling complexes. Validation of Alk proximitome candidates further revealed co-expression of Stardust (Sdt), Discs large 1 (Dlg1), Syntaxin (Syx) and Rugose (Rg) with Alk in the CNS and identified the protein-tyrosine-phosphatase Corkscrew (Csw) as a modulator of Alk signaling.